What Shall I Be? - Ideas For Dressing Up - Ray Gibson (Usborne Publishing Ltd, 2003)
This addition to the What Shall I Do Today? series presents a variety of ideas for children who enjoy dr essing up. The author shows how, using only a few simple clo thes and objects, one can be transformed into a doctor, mons ter, scarecrow, etc. '
Keywords: PY - Arts -- PY - Arts